Multi-objective Optimization Research on the Hydraulic End Structure of Pump Valve Seats - Zhang, Qi; Shao, Jun; Wang, Jiawei; Qin, Haowei (Scientific Journal of Technology, 2026)
In view of the problems such as leakage, water hammer impact and severe wear of mud pump valve seats under harsh working conditions, this paper takes the new hydraulic end valve seat as the research object, selects key design variables, and constructs a multi-objective optimization model with the goals of minimizing leakage, peak water hammer pressure and wear. Through single-parameter analysis and multi-parameter coupling optimization, the influence laws and coupling effects of parameters on performance are revealed, and the performance of related optimization algorithms is compared and analyzed. The research achieved a multi-objective balance of leakage, water hammer pressure suppression and wear reduction, and determined the optimal combination of structural parameters. This scheme effectively enhances the volumetric efficiency, operational reliability and service life of the mud pump, providing a feasible technical solution and scientific basis for the equipment upgrade of mud pumps in the field of oil drilling.